INOVASI PELATIHAN MAKANAN SEHAT DAN BERGIZI SEBAGAI STRATEGI PENCEGAHAN MALNUTRISI DI MASYARAKAT - Luluk Firdausiyah; Fitri Handayani Simatupang; Laily Jelita Harahap (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program was implemented in Central Tapanuli Regency with the aim of increasing community capacity in addressing malnutrition through innovative training in preparing healthy and nutritious food. The background of the activity is based on the persistently high number of cases of malnutrition among toddlers and school children, which is generally triggered by unbalanced consumption patterns and a lack of family knowledge about nutritious menu variations. The implementation method used a participatory approach, involving Posyandu cadres, housewives, PAUD teachers, and village youth. The activity stages began with identifying local nutritional needs, followed by training in creating menus based on local food ingredients such as fish, vegetables, and tubers. The innovative training emphasized the combination of traditional recipes with modern techniques, so that the food was not only nutritious, but also practical and attractive to children. The implementation results showed an increase in participants' knowledge about balanced nutrition and skills in processing local food ingredients into healthy meals. Questionnaire evaluations showed that 78% of participants began routinely implementing the new menus at home. In addition, a group of mothers concerned with nutrition was formed, which functions as agents of change at the community level. This program demonstrates that innovative training based on local potential can be an effective strategy in preventing malnutrition and strengthening food security in the Central Tapanuli community.